Prospek Varietas Toleran dalam Pengendalian Hama Kutu Kebul pada Kacang Tanah - Kasno, Astanto; Suharsono, Suharsono; Trustinah, Trustinah (Buletin Iptek Tanaman Pangan, 2015)
The status of whitefly (Bemisia tabaci Genn.) as a major pest of groundnut had increased in the past few years. Severe pest attacks occurred in the hot and dry season caused significant groundnut yield loss. An effective component of whitefly control is the use of resistant varieties since it has a wide host range. Evaluation of groundnut for resistant germplasms had been carried out with resistant criteria as a basis for the assesment. So far there has been no resistant groundnut genotypes identified as indicated by the number of whiteflies observed on each of groundnut genotype (256 whiteflies per accession). The resistance was defined as the ability of plants to grow under the pest infestation and produce acceptable yield. In this study, the pod yield criteria for resistance to whitefly were set up as follow: >1.2 t/ha = resistant (R); 1.0 to 1.2 t/ha = moderately resistant (MR), and <1.0 t/ha = susceptible (S). Based on these criteria and selection limit of 50% pod yield, 15 groundnut genotypes were found resistant to whitefly with pod yields ranging from 1.2-2.0 t/ha dry pods. Three groundnut varieties that resistant to whitefly were Takar 1, Talam 1, and Landak. Among these varieties, Takar 1 was the most resistant variety to whitefly. In order to maintain the resistance and to avoid the development of new strains of whiteflies, it is suggested that the planting of resistant groundnut should be integrated with selective use of insecticides.